Influence of parity, maternal age and gestational age at birth weight - Herrera, César (2015)
OBJECTIVE: To determine if maternal age, parity and gestational age have influence in the weight of the newborn, in 730 normal pregnant women that had normal delivery at the Obstetrical Service of HVLE-IPSS, Trujillo, from August 1, 1995 through March 31, 1996. Statistical analysis used Chi square. RESULTS: - 03% of newborns had low weight (< 2500g) and 5,8% had macrosomy (> 4000 g). Average newborn weight was influenced by gestational age: preterm (6,8%) weighed 2570 g, term newborns (89,1%) 3552 g, and postterm newborns (3%) 3552g (P < 0,01). Average weight af the newborn was influenced by parity: first pregnancies (38,9%) with 3090 g, multiparae (53,7%) 3273 g, and rand multiparae (7,4%) 3371 g (P < 0, 001). - Average weight of the newborn was influenced by maternal age: adolescents (0,86%) 3120 g, 20 to 24 year-old (19,44%) 3183 g, 25 to 29 year-old (34,6%) 3283 g, 30 to 34 year-old (25,4%) 3302 g, 35 to 39 year-old (13,7%) 3239 g, and 40 to 44 year-old (5,4%) 3134 g (P < 0,01). CONCLUSION: Parity, maternal age and gestational age influence significatively on the weight of the newborn.